2017
DOI: 10.2147/ott.s132062
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of nodal skip metastasis in resectable thoracic esophageal squamous cell carcinoma

Abstract: PurposeThis study aimed to investigate the incidence of nodal skip metastasis (NSM) to identify the risk factors that influence NSM and to assess the prognostic value of NSM in patients with thoracic esophageal squamous cell carcinoma (ESCC).Patients and methodsBetween January 2009 and December 2013, 285 patients with ESCC with positive lymph nodes who underwent complete resection were enrolled.ResultsFor the entire group, NSM occurred in 32.3% (92/285) of patients. The median survival time and 5-year survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Given that the mechanism of lymph node metastasis may be related to the lymphatic drainage, micrometastasis and the biological behavior of tumor cells at the anatomical location of the tumor, the favorable prognosis of NSM patients may be related to the following factors. First, in this study, the grouping of 321 patients before PSM showed that the proportion of patients at the earlier T stage and N stage was higher in the NSM group than in the NNSM group, which was similar to many previous related studies (4,8,9,(16)(17)(18). Second, the number of sites of metastatic nodes also affected the prognosis of patients undergoing surgery for esophageal cancer (19).…”
Section: Discussionsupporting
confidence: 87%
“…Given that the mechanism of lymph node metastasis may be related to the lymphatic drainage, micrometastasis and the biological behavior of tumor cells at the anatomical location of the tumor, the favorable prognosis of NSM patients may be related to the following factors. First, in this study, the grouping of 321 patients before PSM showed that the proportion of patients at the earlier T stage and N stage was higher in the NSM group than in the NNSM group, which was similar to many previous related studies (4,8,9,(16)(17)(18). Second, the number of sites of metastatic nodes also affected the prognosis of patients undergoing surgery for esophageal cancer (19).…”
Section: Discussionsupporting
confidence: 87%
“…When tumor cells penetrate the esophageal wall through longitudinal drainage ducts and subsequently traverse transverse drainage ducts, there is a higher possibility of bypassing lymph nodes near the primary tumor and metastasizing to more distant lymph nodes, promoting the development of lymph node skip metastasis ( 22 , 23 ). Furthermore, a Japanese study found that lymphatic skip metastasis in thoracic esophageal carcinoma was associated with the absence of lymphatic vessels between the middle mediastinum and supraclavicular muscles.…”
Section: Mechanism Of Esophageal Cancer Metastasismentioning
confidence: 99%
“…Table 3 shows the characteristics of eligible studies. This meta-analysis included a total of 9 studies [5,[14][15][16][17][18][19][20][21] published from 2010 to 2021. Seven studies were reported in China, one was from Germany and the remained one originated from Italy.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All 9 studies [5,[14][15][16][17][18][19][20][21] including 4106 patients reported the association between NSM and OS. Statistical heterogeneity was significant (v 2 = 57.81, P \ 0.001, I 2 = 86.2%).…”
Section: Meta-analysismentioning
confidence: 99%